SIX SIGMA AND QUALITY COST ANALYSIS IN IMPROVING PROFIT - Felisia Sutomo (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2021)
Quality is one of the key success factors to achieve competitive advantage. When companies succeeded to improve quality of the service or product given, they will have the possibility to increase their market share and eventually their profit. One of the methods to increase quality is by doing six sigma analysis that focuses on the cause of the problem. The research is done in PT Cemara Agung, one of textile industries in Indonesia. Research method used is descriptive study. Literature study, observations, and interviews has been done in order to search root cause and generate recommendations. The analysis shows that almost fifty percent of the main cause in defect products is happened to the weaving department, which then cause the profit of the company decreased as an impact of the spoilage produced. By doing six sigma analysis and finding recommendations to resolve the problems, the company is expected to be able to reduce the quality cost, increase the quality and eventually increase the profit of the company.